Aging attenuates adenosine triphosphate‐induced, but not muscarinic and nicotinic, cutaneous vasodilation in men. (19th June 2018) - Fujii, Naoto; Nishiyasu, Takeshi; Sigal, Ronald J.; Boulay, Pierre; McGarr, Gregory W.; Kenny, Glen P.
Abstract: Objective: We evaluated the hypothesis that aging attenuates muscarinic, nicotinic, and ATP‐related cutaneous vasodilation. Methods: In 11 young (24 ± 4 years) and 11 older males (61 ± 8 years), CVC was assessed at 3 forearm skin sites that were infused with either: (i) methacholine (muscarinic receptor agonist, 5 doses: 0.0125, 0.25, 5, 100, 2000 mmol/L), (ii) nicotine (nicotinic receptor agonist, 5 doses: 1.2, 3.6, 11, 33, 100 mmol/L), or (iii) ATP (purinergic receptor agonist, 5 doses: 0.03, 0.3, 3, 30, 300 mmol/L). Each agonist was administered for 25 minutes per dose. Results: We showed that CVC at all doses of methacholine did not differ between groups. Similarly, no between‐group differences in CVC were observed during nicotine administration at all doses administered. By contrast, while no differences in CVC were measured during the administration of ATP at low (0.03 and 0.3 mmol/L) or high (300 mmol/L) concentrations, CVC was reduced in the older relative to the young males at moderate concentrations of ATP (3 mmol/L: 23 ± 6 vs 40 ± 13%max, 30 mmol/L: 62 ± 11 vs 83 ± 8%max, both P ≤ .05). Conclusions: We show that aging attenuates ATP‐induced, but not muscarinic or nicotinic, cutaneous vasodilation in men.